Engineering the Active Site Pocket to Enhance the Catalytic Efficiency of a Novel Feruloyl Esterase Derived From Human Intestinal Bacteria Dorea formicigenerans - Shen, Yang; Wang, Yulu; Wei, Xue; Wen, Boting; Liu, Shujun; Tan, Huishuang; Zhang, Jingjian; Shao, Shuli; Xin, Fengjiao (Frontiers in Bioengineering and Biotechnology, 2022)
The human gut microbiota play essential roles in metabolism and human health, especially by enzymatically utilizing dietary fiber that the host cannot directly digest and releasing functional components including short-chain fatty acids (SCFAs) and hydroxycinnamic acids (e.g., ferulic acid). In our previous study, seven potential feruloyl esterase (FAE) genes were identified from the gut microbiota. In the current work, one of the genes encoding a novel FAE (DfFAE) from Dorea formicigenerans of Firmicutes was bacterially expressed, purified and characterized. The 30.5 kDa type-A DfFAE has an optimum pH and temperature of 8.4 and 40°C, respectively, exhibiting a higher substrate specificity toward short-chain acyl-ester substrate (pNPA). The AlphaFold2 based ab initio structural modeling revealed a five α-helices cap domain that shaped an unusually narrow and deep active site pocket containing a specific substrate access tunnel in DfFAE. Furthermore, rational design strategy was subjected to the active site pocket in an aim of improving its enzymatic activities. The mutants V252A, N156A, W255A, P149A, and P186A showed 1.8 to 5.7-fold increase in catalytic efficiency toward pNPA, while W255A also exhibited altered substrate preference toward long-chain substrate pNPO (45.5-fold) by creating an additional substrate access tunnel. This study highlighted an unusual active site architecture in DfFAE that influenced its substrate selectivity and illustrated the applicability of rational design for enhanced enzymatic properties.